Reforming Criminal Sentencing: The Installment-Based Imprisonment Model as an Equitable Alternative - Siswanto Siswanto; Ariesta Wibisono Anditya (IJCLS (Indonesian Journal of Criminal Law Studies), 2026)
This study examines the normative and theoretical foundations of installment-based imprisonment as a progressive alternative in contemporary sentencing reform. It argues that a modular custodial model can enhance fairness, proportionality, and flexibility by addressing major criticisms of conventional imprisonment, particularly socio-economic inequality, structural rigidity, and the limited capacity of prison sanctions to support restorative goals. Using normative legal research, this study combines statutory, conceptual, comparative, and futuristic approaches to analyze legal materials and identify both doctrinal limitations and future reform opportunities. Through a descriptive-prescriptive framework, the research maps the current legal landscape and formulates recommendations for restructuring custodial sanctions in line with equitable punishment, penal rationality, and individualized justice. Content analysis is employed to reveal recurring patterns, normative inconsistencies, and tensions within existing sentencing practices. The findings suggest that installment-based imprisonment could reduce prison overcrowding, lessen the socio-economic harm caused by continuous incarceration, support reintegration, and promote more humane penal policies without undermining offender accountability. It also encourages sentencing adaptability and prevents excessive punitive consequences in practice. By integrating doctrinal analysis, comparative perspectives, and forward-looking legal reasoning, this study concludes that installment-based imprisonment offers a viable and ethically grounded model for criminal sentencing reform.